Wood Basic Density Variation Along Pinus occidentalis , Swartz, and Pinus caribaea , var. Caribaea, Morelet tree stems - Santiago Wigberto Bueno-López; Luis René Caraballo-Rojas; Juan Gilverto Torres-Herrera (Floresta e Ambiente)
Abstract Pinus occidentalis and Pinus caribaea are important conifers in La Sierra, Dominican Republic, used to recover degraded ecosystems. A study on their wood density obtained from stem discs at three relative heights (RH) as a composite sample showed that wood density increased with age class for both species and decreased with RH in the stem. A mixed repeated measures analysis of variance, followed by a regression approach to the effects model, indicates a statistically significant interaction between species, age class (AC), RH, [ , P ≤0.000, partial =0.814]. Simple bidirectional interactions between factors and all simple main effects are statistically significant. Basic density (BD) increased with age class for both species and decreased with RH in the stem. Pinus occidentalis had a 14.6% higher average wood density and is endemic. Therefore, efforts must be made to provide better silvicultural practices so that its population continues to be a viable asset.